Foreword - Schulmann,K.; Vrana,S. (Journal of the Czech Geological Society, 1995)
This issues contains abstracts of lectures and posters submitted to the conference. Recent advances in structural geology, tectonics, petrology and seidmentology call for integration of our observations and thinking about dynamic processes in the lithosphere. The objective of the conference was to include state-of-the-art perspectives that will clearly indicate directions for future research. Four major conference topics were therefore selected to cover a wide spectrum of modern tectonic research: tectonic environment and metamorphism; magma flow and emplacement; crustal rheology & lithosphere deformation; and tectonic controls of basin evolution.